Feed Intake and Behavioural Performance of Osmanabadi Kids on Different Flooring Systems - Wakchaure, M. B.; Kharwadkar, M. D.; Siddiqui, M. F.; Ingle, V. S.; Telange, N. P.; Sonawane, A. S. (International Journal of Livestock Research, 2020)
An experiment was planned to study the feed intake and behavioural performance of Osmanabadi kids following different flooring systems.28 Osmanabadi kids of similar age, body weight and either sex were kept on different floorings i.e. T0 -Concrete floor, T1 - Soil floor, T2 -Murrum floor and T3 -Sand floor. The overall means of daily feed intake (g/d) was significantly higher in T2 (679.33±13.41), T1 (594.17±9.35) and T0 (493.88±7.55) than T3 (480.68±8.91). The overall means of rumination behaviour shown by kids for T0, T1, T2 and T3 were 382.83±7.19, 389.50±7.21, 402.00±4.76 and 390.83±6.51 min/24hrs, respectively. The overall means of agonistic behaviour shown by kids for T0, T1, T2 and T3 were 42.16±1.01, 41.16±2.40, 39.83±2.19 and 40.83±2.18 min/24hrs, respectively. The overall means of resting behaviour was significantly higher in T2 (458.83±4.38), T1 (447.00±2.91) and T3 (439.33±2.91) than T0 (435.83±6.84). It was concluded that murum type of flooring material is comparatively superior with other different types of flooring.